Prosthetic valve endocarditis caused by multidrug-resistant Candida albicans in a patient with myelodysplasia syndrome: A case report and literature review - Firoozeh Kermani; Tahereh Shokohi; Mahdi Abastabar; Lotfollah Davoodi; Shervin Ziabakhsh Tabari; Rozita Jalalian; Shirin Mehdipour; Roghayeh Mirzakhani (Mazandaran University of Medical Sciences, 2018)
Background and Purpose: Candida endocarditis is an infrequent disease with a high mortality rate, which commonly occurs in immunosuppressed patients with cardiac valve replacement. We reported a 70-year-old woman diagnosed with Candida prosthetic valve endocarditis (PVE). This study also involved a review of all published cases of Candida PVE from 1970. Case report: Herein, we reported a 70-year-old woman with the history of severe mitral stenosis and myelodysplasia syndrome. She underwent mitral valve replacement for two times. The blood cultures were positive, and phenotypic identification of the isolates at the species level was performed based on microscopic and macroscopic characteristics. In the second prosthetic valve replacement, huge fungal white and creamy vegetation was observed which was identified as Candida albicans based on the conventional and molecular methods. Despite the administration of antifungal treatments, the patient passed away probably due to the multidrug-resistant Candida PVE. Conclusion: As PVE is a late consequence of prosthetic valve replacement, extended follow-up visits, early diagnosis, repeating valve replacement surgeries, and timely selective antifungal treatments are warranted. Keywords: Amphotericin B, Antifungal resistant, Azoles, Candida endocarditis, Multi-drug resistant, Myelodysplasia syndrome, Prosthetic valve replacement